2020
DOI: 10.1101/2020.08.12.20173609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frontline healthcare workers’ knowledge and perception of COVID-19 and willingness to work during the pandemic in Nepal: a nationwide cross-sectional web-based study

Abstract: Background The health sector's effectiveness during a pandemic primarily depends on the availability, knowledge, skills, perceptions, and motivations of frontline healthcare workers. In this study, we aimed to investigate the contextual factors associated with the knowledge, perceptions, and the willingness of frontline healthcare workers to work during the COVID-19 pandemic in Nepal. Methods A total of 1051 frontline health-workers from all seven Nepalese provinces were included in this web-based cross-sect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…However, this caused a moral dilemma between a duty to treat and a right to refrain. Our ndings are consistent with a study conducted in Nepal where 35.9% of HCWs showed an unwillingness to work during the pandemic (24). In Bangladesh, it is reported that the reluctance of some physicians to treat patients suspected of COVID-19 infection, was due to personal risk assessment and not to reliable objection (25).…”
Section: Baseline Characteristicssupporting
confidence: 91%
“…However, this caused a moral dilemma between a duty to treat and a right to refrain. Our ndings are consistent with a study conducted in Nepal where 35.9% of HCWs showed an unwillingness to work during the pandemic (24). In Bangladesh, it is reported that the reluctance of some physicians to treat patients suspected of COVID-19 infection, was due to personal risk assessment and not to reliable objection (25).…”
Section: Baseline Characteristicssupporting
confidence: 91%
“…The results could provide a guide to hospitals’ decision-makers in order to have under control the situation of the Algerian healthcare system [ 46 ] and for the other countries healthcare systems, because our findings are in consensus with the results of the other researchers [ 47 , 48 , 49 ]…”
Section: Discussionsupporting
confidence: 88%
“…A considerable proportion of respondents also held the misconception that antimalarials are a method of prevention, an opinion that may promote selfmedication among health workers, and lead to delayed diagnosis and treatment. The finding of better knowledge among doctors and nurses has been reported in other studies (13,15) and may be due to differences in levels of technical knowledge between the groups and the preference to train doctors and nurses over other categories. Efforts should be put into ensuring other categories of health workers are trained.…”
Section: Discussionsupporting
confidence: 77%
“…The success of any response mounted against the COVID -19 pandemic in the country will depend heavily on the knowledge level, availability, and willingness to work of frontline health workers. The study showed majority of the respondents had good knowledge of COVID-19, a finding shared by studies in Nepal (82.8%) (13). Chine (88.4%) (14) and Ghana (65.1%) (15).…”
Section: Discussionmentioning
confidence: 61%